A Study on Health Seeking Behaviors of Patients of Post-Kala-Azar Dermal Leishmaniasis. (15th December 2015) - Basher, Ariful; Nath, Proggananda; Nabi, Shah Golam; Selim, Shahjada; Rahman, Md Fashiur; Sutradhar, Satya Ranjan; Faiz, Abul; Bhuiyan, Matiur Rahman; Ahmed, Be-Nazir; Rahman, Ridwanur
Abstract : Post-Kala-Azar Dermal Leishmaniasis (PKDL) remains a major public health threat in Bangladesh. A cross-sectional study was carried out in Surya Kanta Kala azar Research Centre (SKKRC), Mymensingh, from January 2012 to July 2013 to evaluate the health seeking behaviour and the length of delay of PKDL management. The consecutive 200 diagnosed PKDL cases that got treatment in SKKRC hospital were subjected to evaluation. Most (98%) of the patients were not aware and had no knowledge about PKDL, though 87.5% had a history of history of Kala-azar treatment. Many patients reported first to village doctor (15.5%), the pharmacy shop (10%), or traditional health provider (7.5%) upon recognition of symptom. The time between the initial symptom recognition and first medical consultation (patient delay) ranged from 10 days to 4745 days (13 years) with a median of 373 days (mean: 696; IQR: 138 to 900 days). The time between first medical consultations to definite treatment (system delay) ranged from 0 days to 1971 days (5.4 years), with a median delay of 14 days (mean: 46.48; IQR: 7 to 44 days) that was reported in this study. Age, education, occupation, and residential status had significant association with patient delay (P < 0.05 ). Educational status, occupation, number of treatment providers, and first health care provider had a significant association with system delay (P < 0.05 ). Success in PKDL diagnosis and treatment requires specific behavior from patients and health care providers which facilitate those practices.